Utility of four-dimensional computed tomography angiography for evaluating the mobility of a thrombus in the ascending aorta - Daisuke Asahara, MD; Toshiki Kuno, MD, PhD; Kiyoshi Koizumi, MD; Takahito Itoh, MD; Yohei Numasawa, MD, PhD; Masaki Kodaira, MD, PhD; Kazuo Isozumi, MD, PhD; Satoru Komatsumoto, MD, PhD (Radiology Case Reports, 2020)
Four-dimensional computed tomography has been used to evaluate moving structures and is a useful method to diagnose cardiovascular diseases. We report a case of cerebral infarction due to the thrombus in the ascending aorta, and utilized 4-dimensional computed tomography angiography for visualizing the movement of the thrombus, which prompted early surgical intervention to prevent further thromboembolism. Although transesophageal echocardiography is an established method to evaluate the ascending aorta, it has some contraindications and complications. Four-dimensional computed tomography angiography is an excellent alternative without blind spots to evaluate the ascending aorta more quickly than transesophageal echocardiography. Keywords: Four-dimensional computed tomography, Thrombus in the ascending aorta